No free speech for fascists - Renton, Dave, 1972- author.
1 online resource.
Keywords: "No Free Speech for Fascists explores the choice of anti-fascist protesters to demand that the opportunities for fascists to speak in public places is rescinded, as a question of history, law, and politics. It explains how the demand to No Platform fascists emerged in 1970s Britain, as a limited exception to a left-wing tradition of support for free speech. The book shows how No Platform was intended to be applied narrowly, only to a right-wing politics that threatened everyone else. It contrasts the rival idea of opposition to Hate Speech that also emerged at the same time and is now embodied in European and British anti-discrimination laws. Both No Platform and Hate Speech reject the American First Amendment tradition of free speech, but the ways in which they reject it are different. Behind No Platform is not merely a limited range of political targets but a much greater scepticism about the role of the state. The book argues for an idea of No Platform which takes on the electronic channels on which so much speech now takes place. It shows where a fascist element can be recognised within the much wider category of far-right speech. This book will be of interest to activists and to those studying and researching political history, law, free speech, the far right, and anti-fascism. It sets out a philosophy of anti-fascism for a social media age"--